The antidepressant fluoxetine alters mechanisms of pre- and post-copulatory sexual selection in the eastern mosquitofish (Gambusia holbrooki). (July 2018) - Bertram, Michael G.; Ecker, Tiarne E.; Wong, Bob B.M.; O'Bryan, Moira K.; Baumgartner, John B.; Martin, Jake M.; Saaristo, Minna
Abstract: Contamination of aquatic habitats with pharmaceuticals is a major environmental concern. Recent studies have detected pharmaceutical pollutants in a wide array of ecosystems and organisms, with many of these contaminants being highly resistant to biodegradation and capable of eliciting sub-lethal effects in non-target species. One such pollutant is fluoxetine, a widely prescribed antidepressant, which is frequently detected in surface waters globally and can alter physiology and behaviour in aquatic organisms. Despite this, relatively little is known about the potential for fluoxetine to disrupt mechanisms of sexual selection. Here, we investigate the impacts of 30-day exposure to two environmentally realistic levels of fluoxetine (low and high) on mechanisms of pre- and post-copulatory sexual selection in the eastern mosquitofish ( Gambusia holbrooki ). We tested 1) male mating behaviour in the absence or presence of a competitor male, and 2) sperm quality and quantity. We found that high-fluoxetine exposure increased male copulatory behaviour in the absence of a competitor, while no effect was detected under male-male competition. Further, fluoxetine exposure at both concentrations increased total sperm count relative to males from the control group, while no significant change in sperm quality was observed. Lastly, low-fluoxetine males showed a significant reduction in condition index (mass relative to length). Our study is the first to show altered mechanisms of both pre- and post-copulatory sexual selection in an aquatic species resulting from environmentally realistic fluoxetine exposure, highlighting the capacity of pharmaceutical pollution to interfere with sensitive reproductive processes in wildlife. Graphical abstract: Image 1 Highlights: Contamination of aquatic habitats with pharmaceutical pollution is widespread. Mosquitofish ( G. holbrooki ) were exposed to fluoxetine (FLX) at two realistic levels. FLX altered male copulatory behaviour, total sperm count and body condition. First study to show FLX-altered pre- and post-copulatory mechanisms of sexual selection. Highlights ecologically important sub-lethal impacts of pharmaceutical pollution. Abstract : The widespread pharmaceutical pollutant fluoxetine alters mechanisms of pre- and post-copulatory sexual selection in fish.